Diagnostic value of progesterone receptor and p53 expression in uterine smooth muscle tumors - Hewedi Iman H; Radwan Nehal A; Shash Lobna S (BMC, 2012)
Abstract Background The diagnosis of uterine smooth muscle tumors depends on a combination of microscopic features. However, a small number of these tumors still pose difficult diagnostic challenges. Aim To investigate progesterone receptor (PR) and p53 expression in leiomyomas (LMs), atypical leiomyomas (ALMs), smooth muscle tumors of uncertain malignant potential (STUMP), and leiomyosarcomas (LMSs) and to evaluate the potential utility of the selected immunohistochemical markers in differentiating these tumors. Materials and methods Immunohistochemical expression of PR and p53 was investigated in 41 uterine smooth muscle tumors comprising: 15 LMS, 4 STUMP, 6 ALM and 16 LM. Quantitative evaluation of PR and p53 expression was graded on a scale from 0 to 3+. Results Leiomyosarcomas showed reduced PR expression. All LMs as well as ALMs and STUMP were stained intensely for PR. Conversely, LMS was strongly stained with p53, while the three non-sarcomatous groups (STUMP, ALM, LM) were either entirely negative or weakly stained for p53. Regarding both PR and p53 expression, the difference between the LMS group and the three non-sarcomatous groups was highly significant (p < 0.001). Combined high PR - low p53 expression was seen in all the 26 examined cases of the non-sarcomatous group including the STUMP cases and none of the LMS cases. Therefore, it represents a "benign" profile with 100% specificity in diagnosis of a non-sarcomatous tumor. Conclusion Immunohistochemistry for PR and p53 is valuable as an adjunct tool to morphological assessment of problematic uterine smooth muscle tumors.